2009
DOI: 10.1128/aem.01563-09
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of an Intracellular Esterase from the Wine-Associated Lactic Acid BacteriumOenococcus oeni

Abstract: We report the cloning and characterization of EstB28, the first esterase to be so characterized from the wine-associated lactic acid bacterium, Oenococcus oeni. The published sequence for O. oeni strain PSU-1 was used to identify putative esterase genes and design PCR primers in order to amplify the corresponding region from strain Ooeni28, an isolate intended for inoculation of wines. In this way a 912-bp open reading frame (ORF) encoding a putative esterase of 34.5 kDa was obtained. The amino acid sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 52 publications
3
78
1
1
Order By: Relevance
“…Mammalian HSLs contain a catalytic domain and an associated unique regulatory module in the N-terminal domain [35]. Family IV carboxylesterases have four conserved sequence motifs: the oxyanion region GGGX, the pentapeptide -GDSAG-signature motif, and two C-terminal conserved motifs, -DPLR-and -HGF- [1,38,46]. The deduced amino acid sequence indicates that EstIM1 is similar to other esterases of family IV, as it also contains a GGGX (N-terminal oxyanion region) motif, the pentapeptide GXSXG (a nucleophilic elbow), a DPLR motif (at position 252-255), and an HGF motif (at position 282-284) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian HSLs contain a catalytic domain and an associated unique regulatory module in the N-terminal domain [35]. Family IV carboxylesterases have four conserved sequence motifs: the oxyanion region GGGX, the pentapeptide -GDSAG-signature motif, and two C-terminal conserved motifs, -DPLR-and -HGF- [1,38,46]. The deduced amino acid sequence indicates that EstIM1 is similar to other esterases of family IV, as it also contains a GGGX (N-terminal oxyanion region) motif, the pentapeptide GXSXG (a nucleophilic elbow), a DPLR motif (at position 252-255), and an HGF motif (at position 282-284) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Esterases that originate from wine LAB are responsible for both the biosynthesis and hydrolysis of esters (Matthews et al, 2004;Sumby et al, 2009;Brod et al, 2010). Oenococcus oeni, as well as species of Lactobacillus and Pediococcus, is able to hydrolyse esters and Matthews et al (2006) found that significant esterase activity levels remained under wine-like conditions.…”
Section: Malolactic Fermentation Must and Wine Composition Before Inomentioning
confidence: 99%
“…Some of the aroma-related enzymes include β-glucosidase, phenolic acid decarboxylase (PAD), citrate lyase, esterase, protease, peptidases, α-acetolactate synthase and α-acetolactate reductase (Spano et al, 2005;Sumby et al, 2009;Brod et al, 2010;Mtshali et al, 2010), as well as enzymes that play a role in the production of volatile sulphur compounds, including S-adenosylmethionine synthase, cystathionine β/γ-lyase and glutathione reductase (Knoll et al, 2010). Other enzymes of interest that play a negative role in the wholesomeness of the wine, besides those enzymes implicated in biogenic amine production, include those that are involved in ethyl carbamate formation, a potential carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…The buffers (100 mM) used were acetic acid-sodium acetate (pH 3 to 5), sodium phosphate (pH 6 to 7), Tris-HCl (pH 8), and glycine-NaOH (pH 9). The optimal temperature was assayed by incubating purified Est_1092 esterase in 50 mM McIlvaine buffer (pH 5.0) at different temperatures (5,20,30,37,40,45,55, and 65°C). For temperature stability measurements, the recombinant esterase was incubated in 50 mM McIlvaine buffer, pH 5.0, at 20, 30, 37, 45, 55, and 65°C for 5, 15, and 30 min and 1, 2, 4, 6, and 20 h. Aliquots were withdrawn at these incubation times to test the remaining activity under standard conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Following induction, the cells were grown at 22°C for 20 h and collected by centrifugation (8,000 ϫ g, 15 min, 4°C). The cells were disrupted, and the Est_1092 protein (GenBank accession number ACT61979.1) was purified by affinity chromatography as described previously (18), except that the bound enzyme was eluted using 150 mM McIlvaine buffer (pH 5.0) (30).…”
Section: Methodsmentioning
confidence: 99%